2020
DOI: 10.1002/ange.202000951
|View full text |Cite
|
Sign up to set email alerts
|

Magnetothermal Microfluidic‐Assisted Hierarchical Microfibers for Ultrahigh‐Energy‐Density Supercapacitors

Abstract: Chemical architectures with an ordered porous backbone and high charge transfer are significant for fiber‐shaped supercapacitors (FSCs). However, owing to the sluggish ion kinetic diffusion and storage in compacted fibers, achieving high energy density remains a challenge. An innovative magnetothermal microfluidic method is now proposed to design hierarchical carbon polyhedrons/holey graphene (CP/HG) core–shell microfibers. Owing to highly magnetothermal etching and microfluidic reactions, the CP/HG fibers mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…6−8 However, the development of high-performance flexible supercapacitors still faces many difficulties, such as low energy density, poor rate performance, and the high cost of large-scale production. 9−11 In contrast to the current commercial carbonbased electrode materials, 12,13 transition metal oxides/hydroxides exhibit higher theoretical capacitance values, 14−17 which help to make up for the low energy density of existing supercapacitors. 18−24 However, the problems such as poor conductivity, inferior reversibility, and slow redox kinetics of transition metal oxides/hydroxides often lead to unsatisfied capacity and rate performance.…”
Section: Introductionmentioning
confidence: 99%
“…6−8 However, the development of high-performance flexible supercapacitors still faces many difficulties, such as low energy density, poor rate performance, and the high cost of large-scale production. 9−11 In contrast to the current commercial carbonbased electrode materials, 12,13 transition metal oxides/hydroxides exhibit higher theoretical capacitance values, 14−17 which help to make up for the low energy density of existing supercapacitors. 18−24 However, the problems such as poor conductivity, inferior reversibility, and slow redox kinetics of transition metal oxides/hydroxides often lead to unsatisfied capacity and rate performance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ionic liquids (ILs), which are organic salts possessing a melting point lower than room temperature, have attracted the mass attention of researchers due to their advantages of high thermal stability, low vapor pressure, and wide voltage window . One of the typical ILs is 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIMBF 4 ), which is composed of 1-ethyl-3-methylimidazolium (EMIM) for cations and tetrafluoroborate (BF 4 ) for anions . EMIMBF 4 as the electrolyte could maximize the working potential of SCs up to 4.0 V, endowing an obvious enhancement of energy density and relatively high ion conductivity for SCs .…”
Section: Introductionmentioning
confidence: 99%
“…15 One of the typical ILs is 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIMBF 4 ), which is composed of 1-ethyl-3-methylimidazolium (EMIM) for cations and tetrafluoroborate (BF 4 ) for anions. 16 EMIMBF 4 as the electrolyte could maximize the working potential of SCs up to 4.0 V, endowing an obvious enhancement of energy density and relatively high ion conductivity for SCs. 17 Hence, fabricating ASCs with EMIMBF 4 electrolyte to obtain increased energy density is a seductive method for facing the challenges in the study of SCs.…”
Section: Introductionmentioning
confidence: 99%
“…13 Recently, carbon materials combining with PANI nanorods arrays have received extensive attention in the application of supercapacitors because of their low cost, good chemical stability, thermal stability, electrical conductivity, and mechanical properties. 18,19 For instance, Yu et al reported that the controllable PANI nanoarray could easily grow onto the surface of reduced graphene oxide nanosheets by chemical oxidation, and the prepared composite as an electrode material had a high specific capacitance (the specific capacitance is 752 F/g at 1 A/ g) and good cycle stability (the specific capacitance could retain 90.8% after 10,000 charge/discharge cycles). 20 Wu et al proposed a high-performance micro-supercapacitor based on a microfluid-oriented core-sheath PNA/graphene (PNA/G) composite fiber electrode.…”
Section: Introductionmentioning
confidence: 99%